Africa's Pulse, No. 16, October 2017 - World Bank Group (World Bank, Washington, DC, 2017)
Following a sharp slowdown over the past two years, a recovery is underway in Sub-Saharan Africa. Gross domestic product (GDP) growth in the region is expected to strengthen to 2.4 percent in 2017 from 1.3 percent in 2016, slightly below the pace previously projected. The rebound is being led by the region's largest economies. In the second quarter of 2017, Nigeria exited a five-quarter recession and South Africa emerged from two successive quarters of negative growth. Economic activity has also picked up in Angola. Elsewhere, an increase in mining output along with a pickup in the agriculture sector is boosting economic activity in metals exporters. GDP growth is stable in non-resource intensive countries, supported by domestic demand. But the recovery is weak in several important dimensions. Regional per capita output growth is forecast to be negative for the second consecutive year, while investment growth remains low, and productivity growth is falling.